math help!? what is (ab-a) ÷ (bc-c)?

(ab-a) ÷ (bc-c)

answer: a÷c

Can you explain step by step how to do it?


if (ab-a) ÷ (bc-c) = a(b-1)/c(b-1)

aren't you substituting 1 into c and a. But I don't know the value..

7 Answers

  • 9 years ago
    Favorite Answer

    Basically what you have to do is factorise the brackets.

    (ab-a) will factorise to a(b-1)

    (bc-c) will factorise to c(b-1).

    Then you have a(b-1) / c(b-1) so then the (b-1) will cancel out leaving a/c.

  • half
    Lv 4
    4 years ago

    commencing: ab + c = bc - a upload a to the two aspects: ab + a + c = bc Subtract c from the two aspects: ab + a = bc - c element* the two aspects: a(b+a million) = c(b-a million) Dividing the two aspects by (b+a million): a = c(b-a million)/(b+a million) To element an expression, you come across the GCF of each and every term interior the expression, then extract that. So in ab+a, the GCF of each and every term is a. as a result, extract the a, by dividing each and every term by a, which components b+a million. The GCF must be integrated for it to have a similar cost because of the fact the unique expression even with the shown fact that, so that's written as a(b+a million).

  • Raj K
    Lv 7
    9 years ago

    (ab-a) ÷ (bc-c)

    ={a(b-1) ÷ {c(b-1)}

    =a ÷c

  • 9 years ago

    ab- a/ bx- c

    = a( b- 1)/c( b-1)

    = a/c

  • How do you think about the answers? You can sign in to vote the answer.
  • 9 years ago

    (ab-a)/(cb-c) =



  • Zarn
    Lv 7
    9 years ago

    (ab - a) can be rewritten as a(b - 1)

    (bc - c) can be rewritten as c(b - 1)

    Therefore, the expression (ab-a) / (bc - c) can be rewritten as (a(b - 1)) / c(b - 1))

    Provided that b - 1 is not zero, then it is easy to see by inspection that (ab-a) / (bc - c) = (a(b - 1)) / c(b - 1)) = a / c

  • Mike G
    Lv 7
    9 years ago

    (ab-a) ÷ (bc-c) =

    a(b-1)/c(b-1) = a/c

Still have questions? Get your answers by asking now.